Pengembangan Potensi Wisata Desa Sumberjo Melalui Revitalisasi Wisata Coban Mrican - Putri Marisna; Wilda Daffania Abidin; Forentina Kerti Pratiwi Sujayanti; Alfian Aji Ardiansyah; Dhian Satria Yudha Kartika (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2024)
Sumberjo Village is one of the villages located in Wonosalam District, Jombang Regency with its beautiful landscape. One of the tourist attractions in Sumberjo Village is Coban Mrican Tourism. However, the development of tourism potential in Sumberjo Village, especially Coban Mrican tourism, has not been maximized. This is evident from the unavailability of adequate access to get to the Coban Mrican tourist location and the lack of specific placement of the sign system. This study uses a qualitative descriptive analysis method using SWOT analysis as a data analysis technique. By carrying out the revitalization, it is hoped that Coban Mrican's tourism potential can have a good impact on the surrounding community and Coban Mrican tourism itself.